Storage of sterile health products, barrier systems and environmental sustainability (Research, Society and Development, 2021)
Objective: To analyze scientific productions about storage of sterile health products, repercussions to the CSSD and environmental sustainability. Method: Integrative literature review, PICo strategy and defined procedures by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) base on the following question: What are the implications of storing sterile health products to the CSSD and the environmental sustainability? Researches carried out from April to June 2021, without defined time, in Portuguese, English and Spanish. Results: studies from Brazil (66,7%). The others were from China, Indonesia, India and United States of America. The year of 2015 was the most prevalent (33,3%). Descriptive (53,3%) and experimental (20%) studies. Conclusion: Storage area requires humidity control, temperature and disinfection. Failures such as incomplete packages, products with expired date, organic wastes after sterilization, clean and dirty materials in the storage required reprocessing. The use of the SMS reduced the rate of resterilization. It was identified the complex reprocessing of the drapes made of cotton. The need for continuing education will enable the review of bad practices as well as the knowledge of recommendations from regulatory agencies that need to be attended.